KOORDINASI PEMERINTAHAN DALAM MENUNJANG KEWENANGAN OTONOMI DESA - Listiana Padagi E.42008023 (FISIP Universitas Tanjungpura Pontianak, 2012)
This study is intended to produce a recommendation how to realize an effective coordination withinthe Village Government in particular coordination between the village government and the BPD in thevillage of Stone Tumbles Sharply Titi Ketapang District. The title of this thesis based on the issues raisedin the village of Batu Sharp that the conflict between the village and the BPD, discrepancies anddiscrepancies of opinion in the process of drafting regulations to determining APBDes and village.This study used a qualitative research model by using the theory of coordination